Convectively injected water vapor in the North American summer lowermost stratosphere. Issue 10 (29th May 2013) - Schwartz, Michael J.; Read, William G.; Santee, Michelle L.; Livesey, Nathaniel J.; Froidevaux, Lucien; Lambert, Alyn; Manney, Gloria L.
Abstract : [1] Anderson et al. (2012) ( A2012 ) report in situ observations of convectively injected water vapor (H2 O) in the North American (NA) summer lowermost stratosphere (LMS), occasionally exceeding 12ppmv. They contend that, in such cold/wet conditions, heterogeneous chemistry on binary water‒sulfate aerosols can activate chlorine, leading to catalytic ozone destruction. Aura Microwave Limb Sounder 100 hPa and 82.5 hPa H2 O measurements show that, indeed, the NA LMS is unusually wet, both in mean values and in outliers reaching 18ppmv. Using A2012 's threshold, 4% (0.03%) of 100 hPa (82.5 hPa) NA July–August observations are cold/wet enough for activation. Cold parcels, whether wet or dry, typically have much less HCl to activate and O3 to destroy than A2012 's initial conditions. Slightly lower concentrations of HCl and O3 in cold/wet parcels are attributable, at least in part, to dilution by tropospheric air. Alarming reductions in NA summer column O3 suggested by A2012 are not seen in the current climate. Key Points: Aircraft encounter convectively injected water in the N American stratosphere. Satellite observations show regions/seasons of stratospheric H2 O enhancement. Associated chlorine activation/ozone loss, if present, is at very low levels.